Do international institutions matter? Socialization and international bureaucrats. (September 2019) - Murdoch, Zuzana; Kassim, Hussein; Connolly, Sara; Geys, Benny
A key component of (neo-)functionalist and constructivist approaches to the study of international organizations concerns staff socialization. Existing analyses of how, or indeed whether, staff develop more pro-internationalist attitudes over time draw predominantly on cross-sectional data. Yet, such data cannot address (self-)selection issues or capture the inherently temporal nature of attitude change. This article proposes an innovative approach to the study of international socialization using an explicitly longitudinal design. Analysing two waves of a large-scale survey conducted within the European Commission in 2008 and 2014, it examines the beliefs and values of the same individuals over time and exploits exogenous organizational changes to identify causal effects. Furthermore, the article theorizes and assesses specified scope conditions affecting socialization processes. Showing that international institutions do, in fact, influence value acquisition by individual bureaucrats, our results contest the widely held view that international organizations are not a socializing environment. Our analysis also demonstrates that age at entry and gender significantly affect the intensity of such value change.